MENINGKATKAN KEMAMPUAN MENGUCAPKAN NAMA BENDA MELALUI PERMAINAN KARTU BERGAMBAR BAGI ANAK TUNAGRAHITA SEDANG - Elyza - (Universitas Negeri Padang, 2012)
This study aims to improve the ability to say the names of objects by using a picture card game. This study uses the approach Reaserch Single Subject (SSR) with AB designs. Research subject is the child's initials X. Their behavior is the target size